Heavenly Cat - Ajamain @ Ag. Ajamain, Dg. Nur Azila; Dominic, Wasti; Ingku, Rinah; Gamparon, Leonard Hemilton; Abbas, Mohd Azlan Shah; Marandan, Finoh; Sahiri, Haslindah; Muhin, Muhammad Nazreen (2016)
Heavenly Cat is cat service and product located in Asia City, Lorong Singgah Mata 5, 88000, Kota Kinabalu that allows all people to send their cats in one location to have their cats cared and loved. Heavenly Cat accepts appointments as well as walk-ins. They also sell retail cat products. Such as, Cat food, apparel, meds and more. While there are a few services like Heavenly Cat, Heavenly cat will excel their customer service because they will focused on the wants and needs of their customers. Through unheralded customer attention, Heavenly Cat will slowly but surely gain market share as it focuses more on caring and love towards the cats, as well as creating long-term relationships with their owners. Lastly Heavenly Cat location will allow it to attract a lot of walk in traffic. People across Malaysia have decided to use our services when they want to fulfil their satisfaction on their cats, for example to have our packages on services to their cats or to make over their cat through different style. Heavenly Cat has foreseen this opportunity to provide the best quality and services to cats and do some activities regarding to their cats, despite their variety of breeds. This has shown that Heavenly Cat has the excellence to be one of the most successful products and services to cats in Malaysia. We, Heavenly Cat, saw the opportunity that this business has the potential to be successful. The people who loves cat always need to take care of their cat but do not have the time for it, so our services will do the job for them. We provide a package with variety of services for their cats. And also fun activities such as photo booth contest, and theme park. Heavenly Cat sees this as a way to prosper in this market, by taking advantage of all of loving cat's need.